Accelerated universities : ideas and money combine to build academic excellence - Altbach, Philip G.; Reisberg, Liz; Salmi, Jamil; Froumin, Isak D. (Global perspectives on higher education, 2018)
"During the past several decades, several "highly-resourced, accelerated research universities" have been established around the world to pursue--and achieve--academic and research excellence. These institutions are entirely new, not existing universities that were reconfigured. Accelerated Universities provides case studies of eight such universities and highlights the lessons to be learned from these examples. Each of the cases is written by someone involved with leadership at the early developmental stages of each university, and provides insights that only senior executives can illustrate. Accelerated Universities shows that visionary leadership and generous funding combined with innovative ideas can yield impressive results in a short time. Universities aspiring to recognition among the top tier of global institutions will find this book indispensable"--